2005
DOI: 10.1158/0008-5472.can-04-3319
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Triterpenoids Cooperate with Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand to Induce Apoptosis of Breast Cancer Cells

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL or Apo2L) has been shown to induce apoptosis specifically in cancer cells while sparing normal tissues. Unfortunately not all cancer cells respond to TRAIL; therefore, TRAIL sensitizing agents are currently being explored. We have identified synthetic triterpenoids, including 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO) and its derivative 1-(2-cyano-3,12-dioxooleana-1,9-dien-28-oyl) imidazole (CDDO-Im), which sensitize TRAIL-resistant cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 27 publications
9
93
0
3
Order By: Relevance
“…Recently, several chemopreventive agents such as triterpenoids, silibinin, and flavopiridol have been shown to induce down-regulation of c-FLIP and subsequent sensitization to TRAIL-induced apoptosis in cancer cells [36][37][38]. In this study, we found that treatment of Caki cells with Wit A induced significant down-regulation of both c-FLIP L and c-FLIP S , suggesting that Wit A-induced loss of c-FLIP expression may underlie the observed sensitization to TRAIL.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, several chemopreventive agents such as triterpenoids, silibinin, and flavopiridol have been shown to induce down-regulation of c-FLIP and subsequent sensitization to TRAIL-induced apoptosis in cancer cells [36][37][38]. In this study, we found that treatment of Caki cells with Wit A induced significant down-regulation of both c-FLIP L and c-FLIP S , suggesting that Wit A-induced loss of c-FLIP expression may underlie the observed sensitization to TRAIL.…”
Section: Discussionmentioning
confidence: 50%
“…Direct NF-κB inhibitors also exert antineoplastic effects in select model systems as shown extensively for CDDO-TFEA and derivatives thereof. [51][52][53][54][55][56][57] These findings are consistent with a favorable therapeutic window for NF-κB inhibitors when used in combination with radiation and, potentially, chemotherapeutic drugs. …”
Section: B a E D C Fsupporting
confidence: 56%
“…FLIP has been found to be overexpressed in many human cancers (Ryu et al, 2001;Zhou et al, 2004;Valnet-Rabier et al, 2005), and has emerged through our work and that of others, as a potential anti-cancer drug target (Hyer et al, 2005;Wilson et al, 2007). Furthermore, XIAP has been found to be overexpressed in several cancers, and small molecule and antisense approaches to target XIAP are in development (Hu et al, 2003;LaCasse et al, 2006).…”
Section: Discussionmentioning
confidence: 73%